Information seeking behaviour of the Social Sciences and Humanities undergraduates of the University of Colombo - Wijetunge, Pradeepa (Library, University of Colombo, Sri Lanka, 2018)
This study deals with the Information Seeking Behavior (ISB) of the Humanities and Social Science (HSS) undergraduates of University of Colombo with four objectives; to study the information resource usage, information seeking process, and the barriers encountered by them in seeking information, and to make recommendations to alleviate the issues. A questionnaire and Focus Group Meetings (FGMs) were used to gather quantitative and qualitative data respectively. Convenient Sampling method was used and the response rate was 82% out of 550 questionnaires and 95 attended the FGMs. SPSS (ver. 22) and manual analyses were used to analyse quantitative and qualitative data. The majority use Internet instead of trusted resources provided by the library, and use self-taught criteria to evaluate information instead of standard methods, majority consult peers for help with information resource usage and, the majority has not had any training in using the library resources or Internet. They encounter several barriers related to the resources, facilities, services and training which discourage them from approaching the library primarily, to satisfy their information needs. The process they adopt to seek and use information conforms to some other information seeking models; however their information seeking behavior does not mature across the academic years as it should be, and an uncertainty with information seeking prevails throughout their undergraduate life. While more research is required to substantiate the gravity of this issue, librarians must collaborate with the faculty to reduce the stress and uncertainty levels encountered by the undergraduates moving from print–paradigm to digital-paradigm, and to transform the students in to digitally literate who can step in to the world of work with confidence.
Keywords: Humanities; information seeking behaviour; Social Sciences